Prototipe Mesin Bank Botol Plastik Menggunakan RFID (Radio Frequency Identification) - Aprilia, Ajeng Rahma; Hidayat, Riki; Wibisono, Agung (LPPM Universitas Negeri Jakarta, 2026)
This research aid to design and create a bank machine prototype of plastic bottles using RFID (Radio Frequancy Identification) as well as the access activating the machine.The method used of design tools to see the positive value for the environment and the local economy. Making these tools along with supporting components such as RFID, LoadcellSensor, Servo Motor and LCD Touchscreen. This tool works in accordance with the principle of conventional waste banks, but the difference is the money generated from onsite plastic bottles will be stored in the RFID card.From the results of this tool design using arduino mega 2560 as the central control system. Control of the system is processed in a software program arduino and forwarded through command signal output on each component. It can be concluded that the bank machine prototype of plastic bottles using RFID systems work as instructed. However, these tools are still many shortcomings in the disposal bottle mechanics. It is expected there will be overall improvement both in terms of quality and in terms of effectiveness. Penelitian ini bertujuan untuk merancang dan membuat prototipe mesin bank botol plastik menggunakan RFID (Radio Frequancy Identification) sebagai pengaktif mesin. Metode yang digunakan adalah metode rancang bangun alat dengan melihat sisi nilai positif bagi lingkungan maupun ekonomi masyarakat. Pembuatan alat ini disertai dengan komponen pendukung seperti, RFID, Sensor Loadcell, Motor Servo dan LCD Touchscreen. Alat ini bekerja sesuai dengan prinsip bank sampah konvensional, namun perbedaannya uang yang dihasilkan dari penukaran botol plastik akan disimpan dalam kartu RFID. Dari hasil rancang bangun prototipe mesin bank botol plastik menggunakan RFID ini memakai Arduino Mega 2560 sebagai kontrol pusat sistem. Pengontrolan sistem ini diolah dalam software program Arduino dan diteruskan melalui keluaran sinyal perintah pada masing-masing komponen. Dapat disimpulkan bahwa prototipe mesin bank botol plastik menggunakan RFID bekerja sesuai perintah yang diingikan. Namun, alat ini masih banyak kekurangan pada mekanik pembuangan botol. Diharapkan akan ada perbaikan secara menyeluruh baik dari segi kualitas maupun segi efektivitas.